Knowledge, Attitudes and Application of Child Safety by Families in Karunrung Village, Rappocini, Makassar - Baharuddin Baharuddin; Nasrullah Nasrullah; Muhasidah Muhasidah; Sri Angriani (Humanistic Network for Science and Technology (HNST), 2018)
Preliminary studies through observation and interviews of 10 parents in the Karunrung Village showed that 6 out of 10 children under five had an accident. This study aims to analyze the relationship between knowledge and attitude with the application of Child Safety, using a cross sectional design. The research subjects were 62 families with children aged 6 months to 6 years, who were selected by total sampling technique. Data were collected through the questionnaire questionnaire, then analyzed using Chi square test. The results showed that the application of Child Safety was determined by family knowledge and attitudes. Keywords: Knowledge, Attitude, Family, Child safety